Stability analysis of seed yield in coriander based on non-parametric methods - Rajput, E V D Sastry, S S (Journal of Spices and Aromatic Crops, 2016)
The present study consisted of evaluation of 42 genotypes in two environments –with full irrigations (called irrigated) and with half the number of normal irrigations (called drought) over three years. ANOVA has indicated significant influence of environments on the expression of seed yield. All types of interactions with genotypes were significant indicating non-linear response of genotypes to environments. Stability analysis indicated significant differences among the ranks of stability of the genotypes. Significant positive correlations were noted among the different non parametric statistics and between corrected and uncorrected seed yield. Similarly there was good correspondence between the scatters of the genotypes obtained with Si(1), Si(2), Si(3) as well as between the scatters of AMMI (mean vs IPCA 1).